Sex, Politics, and U.S. District Court Outcomes: Examining Variation in Judge-Initiated Downward Guideline Departures - Crow, Matthew (American journal of criminal justice, 2023)
Disparity in sentencing outcomes continues to garner considerable attention in the research literature. Much of the extant literature focuses on the impact of case-level, and to a lesser extent, court-level characteristics on individual sentencing outcomes. At the federal level, recent research by the United States Sentencing Commission (USSC), however, demonstrates significant disparity across U.S. District Courts in aggregate-level outcomes. Specifically, there is considerable disparity in the rates of judge-initiated guidelines departures across U.S. District Courts. The current study examines whether judicial composition and caseload characteristics impact this disparity using panel data. Results indicate that judicial sex and political composition of districts influence judge-initiated guidelines departure rates.